LINGUODIDACTIC ASPECT OF THE PROFESSIONAL COMMUNICATIVE COMPETENCE - L. S. Znikina (Вестник Кемеровского государственного университета, 2013)
The issues of linguodidactic aspect of forming the professional communicative competence of a modern specialist are considered in the article; the structural and functional components of this competence are analyzed; the explanation of the professional communicative competence as the important instrument in the professional activities of the specialist is given; the role of the cross-cultural interaction is presented.